2013
DOI: 10.1007/s00234-013-1210-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic evaluation of stasis filling phenomenon with computed tomography in diagnosis of brain death

Abstract: IntroductionStasis filling, defined as delayed, weak, and persistent opacification of proximal segments of the cerebral arteries, is frequently found in brain dead patients. This phenomenon causes a major problem in the development of reliable computed tomographic angiography (CTA) protocol in the diagnosis of brain death (BD). The aim of our study was to characterize stasis filling in the diagnosis of BD. To achieve this, we performed a dynamic evaluation of contrast enhancement of the cerebral and extracrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 14 publications
(15 reference statements)
2
34
0
Order By: Relevance
“…As previous studies using CTA showed intracranial vessels in these patients are markedly thinner, and their opacification, regardless it’s level, is significantly weaker than normal [14]. Moreover, cerebral vessels are frequently obscured by subarachnoid hemorrhage (SAH) or increased density of subarachnoid space due to pseudosubarachnoid hemorrhage (pseudoSAH) phenomenon, which are frequently found in this group of patients.…”
Section: Introductionmentioning
confidence: 75%
“…As previous studies using CTA showed intracranial vessels in these patients are markedly thinner, and their opacification, regardless it’s level, is significantly weaker than normal [14]. Moreover, cerebral vessels are frequently obscured by subarachnoid hemorrhage (SAH) or increased density of subarachnoid space due to pseudosubarachnoid hemorrhage (pseudoSAH) phenomenon, which are frequently found in this group of patients.…”
Section: Introductionmentioning
confidence: 75%
“…CTA—Contrast opacification was assessed as a binary outcome of yes/no for extracranial vessels, intracranial internal carotid artery (ICA) (supraclinoid), middle cerebral artery (MCA) branches (M1, M2), anterior cerebral artery (ACA) branches (A1, A2), intracranial vertebral artery, intracranial basilar artery, internal cerebral vein, and vein of Galen. CTA was assessed on 4‐point, 7‐point, and 10‐point scales …”
Section: Methodsmentioning
confidence: 99%
“…The complete absence of intracranial vascular enhancement supports the diagnosis of brain death. However, delayed, weak and persistent opacification of the proximal segments of the cerebral arteries, termed "stasis filling," indicates the inability to perform brain perfusion and should be recognized as an important pitfall when computed tomography angiography (CTA) is analyzed 2,3 . Computed tomography perfusion (CTP) is reliable in demonstrating the absence of brain perfusion and thereby confirming severe hemodynamic arrest 4,5 (Figure).…”
Section: Reginaldo Carlos Bonimentioning
confidence: 99%